Commentary on Defining the Problem - Vamoer, Alexander P. (International Food Policy Research Institute, 1987)
Kumar's summary of the nutritional problems in sub-Saharan Africa indicates that African countries have generally not perceived malnutrition as pervasive. This problem should be viewed in its historical context. Before independence, most eastern and southern African countries, with the probable exception of Uganda, had very little data on the prevalence of malnutrition. Since then, a number of surveys have established the magnitude of the problem. In countries where such data is now available, it is concentrated largely in aggregates such as national statistics on food production, supply, or consumption. It must be disaggregated to provide information on specific risk groups in the population likely to be affected by development policies and programs.